Adaptation response to pitch shift during speech is attenuated upon relearning - Gaines, Jessica L.; Dale, Corby L.; Houde, John F.; Nagarajan, Srikantan S. (Frontiers in Human Neuroscience, 2026)
IntroductionDuring sensorimotor adaptation, participants respond to a persistent sensory error by shifting behavior to oppose the error. This phenomenon has been measured in multiple motor tasks in which sensory feedback is experimentally altered to artificially introduce an error. Tasks involving multiple cycles of altered and unaltered feedback have been used in the arm reaching domain to understand the mechanisms of un-learning and re-learning a response to an error, but re-learning within a single session has not been studied in the domain of fundamental frequency (f0) control during speech.MethodsIn this study, participants responded to three alternating blocks of f0-shifted and unshifted auditory feedback during a single-word speech task.ResultsIt was found that on average, adaptation magnitude decreased in the second and third blocks of shifted feedback compared to the first. This illustrates an attenuation effect similar to that observed in studies of implicit learning in arm reaching tasks.DiscussionThese results support the understanding of f0 control as an implicit learning phenomenon and help place f0 control in the context of motor control in general.